ProBDNF and Brain-Derived Neurotrophic Factor Prodomain Differently Modulate Acetylcholine Release in Regenerating and Mature Mouse Motor Synapses - Bogacheva, Polina O.; Molchanova, Anastasia I.; Pravdivceva, Ekaterina S.; Miteva, Anna S.; Balezina, Olga P.; Gaydukov, Alexander E. (Frontiers in Cellular Neuroscience, 2022)
TThe effects of brain-derived neurotrophic factor (BDNF) processing by-products (proBDNF and BDNF prodomain) on the activity of mouse neuromuscular junctions (NMJs) were studied in synapses formed during the reinnervation of extensor digitorum longus muscle (m. EDL) and mature synapses of diaphragm. The parameters of spontaneous miniature endplate potentials (MEPPs) and evoked endplate potentials (EPPs) were analyzed in presence of each of the BDNF maturation products (both – 1 nM). In newly-formed NMJs, proBDNF caused an increase in the resting membrane potential of muscle fibers and a decrease in the frequency of MEPPs, which was prevented by tertiapin-Q, a G-protein-coupled inwardly-rectifying potassium channels (GIRK) blocker, but not by p75 receptor signaling inhibitor TAT-Pep5. proBDNF had no effect on the parameters of EPPs. BDNF prodomain in newly-formed synapses had effects different from those of proBDNF: it increased the amplitude of MEPPs, which was prevented by vesamicol, an inhibitor of vesicular acetylcholine (ACh) transporter; and reduced the quantal content of EPPs. In mature NMJs, proBDNF did not influence MEPPs parameters, but BDNF prodomain suppressed both spontaneous and evoked ACh release: decreased the frequency and amplitude of MEPPs, and the amplitude and quantal content of EPPs. This effect of BDNF prodomain was prevented by blocking GIRK channels, by TAT-Pep5 or by Rho-associated protein kinase (ROCK) inhibitor Y-27632. At the same time, BDNF prodomain did not show any inhibitory effects in diaphragm motor synapses of pannexin 1 knockout mice, which have impaired purinergic regulation of neuromuscular transmission. The data obtained suggest that there is a previously unknown mechanism for the acute suppression of spontaneous and evoked ACh release in mature motor synapses, which involves the activation of p75 receptors, ROCK and GIRK channels by BDNF prodomain and requires interaction with metabotropic purinoreceptors. In general, our results show that both the precursor of BDNF and the product of its maturation have predominantly inhibitory effects on spontaneous and evoked ACh release in newly-formed or functionally mature neuromuscular junctions, which are mainly opposite to the effects of BDNF. The inhibitory influences of both proteins related to brain neurotrophin are mediated via GIRK channels of mouse NMJs.